Glass flake amorphous alloy composite anti-corrosion composition, anti-corrosion coating comprising composition and preparation method of glass flake amorphous alloy composite anti-corrosion coating

By combining glass flakes with micro-sheet amorphous alloys, a modified anticorrosion coating is formed, which solves the problem of poor performance of existing anticorrosion coatings in various environments, and achieves the improvement of the overall performance of the coating.

CN119592117APending Publication Date: 2025-03-11CHINA CONSTR EIGHT ENG DIV CORP LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411894092.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing anticorrosion coatings have poor performance in adhesion, wear resistance, impact resistance, salt spray resistance, acid resistance and alkali resistance, resulting in rapid degradation of the coating in harsh environments.

Method used

Using a glass flake amorphous alloy composite anticorrosion composition, the micro-sheet amorphous alloy is combined with the surface modified glass flakes to form a synergistic coating structure to improve the overall performance of the coating.

Benefits of technology

It significantly improves the adhesion, wear resistance, salt spray resistance, impact resistance, acid resistance and alkali resistance of the coating, and has significant performance advantages compared with traditional organic solvent epoxy zinc-rich anticorrosion coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592117A_ABST
    Figure CN119592117A_ABST
Patent Text Reader

Abstract

The invention provides a glass flake amorphous alloy composite anti-corrosion composition. Comprising micron flake amorphous alloy and glass flake # imgabs0, wherein the glass flake # imgabs0 is subjected to surface modification through a mixed solution of a surfactant and a diluent as shown in a formula (I). The invention further provides an anticorrosive coating comprising the glass flake amorphous alloy composite anticorrosive composition and a preparation method of the anticorrosive coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anti-corrosion coatings, and specifically relates to a glass flake amorphous alloy composite anti-corrosion composition, an anti-corrosion coating comprising the composition, and a preparation method thereof. Background Art

[0002] Steel structure anti-corrosion coatings can provide effective anti-corrosion protection for steel structures, extend their service life, and reduce maintenance costs. Steel structures are widely used in the construction industry due to their high strength, plasticity, and toughness, but they also face corrosion problems, especially in harsh environments and industrial areas. Corrosion can lead to a decrease in structural strength and increase safety risks. Anti-corrosion coatings effectively slow down or prevent the contact between corrosive media and metal surfaces through mechanisms such as physical barriers, electrochemical protection, and passivation, thereby protecting steel structures from corrosion. In addition, anti-corrosion coatings also have shielding and corrosion inhibition effects and appearance decoration effects. They can not only prevent corrosive media and moisture from contacting the material surface, improve the anti-corrosion ability of the coating, and delay the occurrence of corrosion, but also provide decorative effects for steel structure projects, allowing them to better integrate into the surrounding environment.

[0003] However, existing anti-corrosion coatings have some problems that limit their performance and application range. Low adhesion is a common problem that can cause the coating to fall off prematurely, especially under dynamic load or mechanical impact, and the insufficient bonding between the coating and the substrate can accelerate the damage of the coating. Poor wear resistance can cause the coating to fail quickly under physical wear, especially in high-flow or high-friction environments, where the coating's insufficient wear resistance can cause it to degrade rapidly. Poor impact resistance can make the coating prone to rupture when impacted by external forces, which is particularly evident on construction sites or in industrial environments. Short salt spray resistance can cause the protective ability of the coating to drop rapidly in salt spray environments such as the ocean, which is a serious problem for steel structures in marine engineering and coastal buildings. Moreover, poor acid and alkali resistance limits the application of anti-corrosion coatings in the field of industrial construction, especially in places corroded by acid and alkali media, where acid and alkali resistant coatings must be used. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a glass flake amorphous alloy composite anti-corrosion composition.

[0005] Another object of the present invention is to provide an anti-corrosion coating comprising the above-mentioned glass flake amorphous alloy composite anti-corrosion composition and a preparation method thereof. The prepared anti-corrosion coating has good adhesion, wear resistance, impact resistance, salt spray resistance, acid resistance, and alkali resistance, and the preparation process is simple, and is suitable for large-scale promotion and application.

[0006] To achieve the above purpose, the solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a glass flake amorphous alloy composite anticorrosion composition, comprising a micron-flaky amorphous alloy and glass flakes surface-modified by a mixed solution of a surfactant and a diluent as shown in formula (I):

[0008]

[0009] In the formula,

[0010] R1, R2, and R3 are each independently selected from an alkyl group or an alkoxy group, wherein the alkyl group in the alkyl group or the alkoxy group is selected from a C1-C8 alkyl group, preferably a C1-C4 alkyl group, more preferably a methyl group, an ethyl group, a methoxy group, or an ethoxy group, wherein R1, R2, and R3 are each the same or different, and at least one of R1, R2, and R3 is an alkoxy group;

[0011] R4 is selected from substituted or unsubstituted C1-C 12 Preferably, R4 is selected from terminal glycidyl ether oxide alkyl, terminal epoxy cycloalkyl alkyl, and the alkyl in the alkyl or cycloalkyl is selected from C1-C8 alkyl.

[0012] Preferably, R4 is selected from the terminal glycidyl ether oxyalkyl group represented by formula (II), the terminal epoxy cycloalkyl alkyl group represented by formula (III):

[0013]

[0014]

[0015] In formula (II), R5 is a C1-C8 alkyl group;

[0016] In formula (III), R6 is a C1-C8 cycloalkyl group.

[0017] Preferably, the surfactant is a silane coupling agent, selected from at least one of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; the diluent is selected from at least one of an active diluent and an inactive diluent, the active diluent is preferably a glycidyl ether diluent, more preferably a cardanol glycidyl ether diluent, the inactive diluent is preferably selected from at least one of cardanol and ethylene glycol monocardanol ether; preferably, the viscosity of the diluent is 5-2000 mPa·s (25°C).

[0018] Preferably, the mixed solution further comprises a solvent, and preferably, the solvent is selected from at least one of dibutyl ether, xylene, n-butanol and 4-methyl-2-pentanone.

[0019] Preferably, the glass flakes are surface treated with the mixed solution by an immersion method or a spraying method, preferably by an immersion method, and more preferably, by an immersion method at room temperature.

[0020] Preferably, the glass flakes are glass flakes formed by crushing hollow glass microspheres and having a lamellar structure with a thickness of 2-20 μm and a flake diameter of 0.01-3.2 mm.

[0021] Preferably, the particle size of the glass flakes is 10-400 mesh, preferably 300-400 mesh.

[0022] Preferably, the micron-sized flaky amorphous alloy is Fe having a lamellar structure. α M β Alloy, wherein M is selected from at least one of the elements Cr, P, C, B, N, Co, Si, Cu, V, Al, Ti, Ta, Nb, Zr, Mo and Ni, preferably, M is selected from at least one of the elements Cr, P, C, B, Si, Cu, Nb and Ni, α and β are atomic percentages, 55≤α≤80, 20≤β≤45, α+β=100; preferably, the particle size of the micron-shaped flaky amorphous alloy is 10-50μm, preferably 20-30μm.

[0023] In a second aspect, the present invention also provides an anti-corrosion coating comprising the glass flake amorphous alloy composite anti-corrosion composition as described above.

[0024] Preferably, the anticorrosive coating comprises component A and component B, wherein:

[0025] Component A includes the following raw materials in parts by weight:

[0026]

[0027] Component B includes the following raw materials in parts by weight:

[0028] 9-12 parts by weight of curing agent;

[0029] Adhesion promoter 1-2 parts by weight.

[0030] Preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin and bisphenol F epoxy resin, and the epoxy equivalent is 350-600g / eq; the pigment is selected from at least one of zinc phosphate, aluminum tripolyphosphate, titanium dioxide, zinc oxide, barium sulfate and talc; the auxiliary agent is selected from at least one of a dispersant, a thickener, a defoamer and a leveling agent; the curing agent is selected from at least one of a phenolic amide curing agent, a polyamide curing agent and a phenolic amine curing agent; the adhesion promoter is selected from at least one of a silane coupling agent, a modified polyester and an acid copolymer.

[0031] In a third aspect, the present invention further provides a method for preparing the anticorrosive coating as described above, comprising the following steps:

[0032] Step (1), mixing and dispersing glass flakes in a mixed solution of a diluent, a surfactant and a solvent, and standing or stirring the mixture at a speed of 400-800 rpm for 15-45 minutes to obtain a sol mixture of surface-modified glass flakes;

[0033] Step (2), mixing the dispersant, epoxy resin, pigment and filler with the sol mixture of glass flakes obtained in step (1), stirring at a speed of 1000-1500 rpm for 45-60 min, then adding micron-flaky amorphous alloy, thickener, leveling agent and defoaming agent at a speed of 800-1000 rpm, stirring for 10-20 min, and obtaining component A;

[0034] Step (3), mixing the adhesion promoter and the curing agent, stirring at a speed of 1000-1500 rpm for 5-10 minutes, to obtain component B;

[0035] Step (4), during construction, the component A obtained in step (2) and the component B obtained in step (3) are mixed, and stirred at a speed of 1000-1500 rpm for 5-10 minutes to obtain an anti-corrosion coating.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The glass flake amorphous alloy composite anti-corrosion composition and the anti-corrosion coating including the composition provided by the present invention have excellent comprehensive properties (including wear resistance, adhesion, salt spray resistance, impact resistance, acid and alkali resistance, etc.) prepared under the synergistic interaction of the surface-modified glass flakes and the micron-shaped flaky amorphous alloy. Compared with organic solvent epoxy zinc-rich anti-corrosion coatings, it has significant performance advantages, and the preparation process is simple, which is suitable for large-scale promotion and application. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below in conjunction with specific implementation methods.

[0039] <Glass flake amorphous alloy composite anticorrosion composition>

[0040] The present invention provides a glass flake amorphous alloy composite anticorrosion composition, comprising a micron-flaky amorphous alloy and glass flakes surface-modified by a mixed solution of a surfactant and a diluent as shown in formula (I):

[0041]

[0042] In the formula,

[0043] R1, R2, and R3 are each independently selected from an alkyl group or an alkoxy group, wherein the alkyl group in the alkyl group or the alkoxy group is independently selected from a C1-C8 alkyl group, preferably a C1-C4 alkyl group, more preferably a methyl group, an ethyl group, a methoxy group, or an ethoxy group, wherein R1, R2, and R3 are each the same or different, and at least one of R1, R2, and R3 is an alkoxy group;

[0044] R4 is selected from substituted or unsubstituted C1-C 12 The alkyl group is a C1-C8 alkyl group, an aralkyl group or a cycloalkyl group.

[0045] In the glass flake amorphous alloy composite anti-corrosion composition of the present invention, the surfactant shown in formula (I) used in the present invention is a silane coupling agent, and conventional silane coupling agents include vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri (β-methoxyethoxy) silane, etc.

[0046] In some preferred embodiments, in the silane coupling agent of formula (I) used in the present invention, R4 is selected from a terminal glycidyl ether oxyalkyl group of formula (II) and a terminal epoxy cycloalkyl alkyl group of formula (III):

[0047]

[0048] In formula (II), R5 is a C1-C8 alkyl group;

[0049] In formula (III), R6 is a C1-C8 cycloalkyl group.

[0050] As an example, the silane coupling agent represented by formula (I) used in the present invention is, for example:

[0051] (1) 3-Glycidyloxypropyltrimethoxysilane:

[0052]

[0053] (2) 3-Glycidyloxypropyltriethoxysilane:

[0054]

[0055] (3) 3-Glycidyloxypropylmethyldimethoxysilane:

[0056]

[0057] (4) 3-Glycidyloxypropylmethyldiethoxysilane:

[0058]

[0059] (5) 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane:

[0060]

[0061] (6) 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane:

[0062]

[0063] In the glass flake amorphous alloy composite anticorrosive composition of the present invention, the diluent used in the present invention is selected from at least one of an active diluent and an inactive diluent. Among them, the active diluent is usually a glycidyl ether diluent, such as glycidyl butyl ether, 2-ethylhexyl glycidyl ether, neopentyl glycol diglycidyl ether, 1,6-ethylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, resorcinol diglycidyl ether or trimethylolpropane glycidyl ether.

[0064] In some preferred embodiments, the active diluent used in the present invention is a cardanol glycidyl ether diluent, for example:

[0065] (1) Cardanol monoglycidyl ether:

[0066]

[0067] (2) Cardanol diglycidyl ether:

[0068]

[0069] In some preferred embodiments, the inactive diluent used in the present invention is, for example:

[0070] (1) Cardanol:

[0071]

[0072] (2) Ethylene glycol monocardanol ether:

[0073]

[0074] In the glass flake amorphous alloy composite anticorrosive composition of the present invention, the glass flakes used in the present invention are flaky glass flakes formed by crushing hollow glass microbeads, having a flaky structure with a thickness of 2-20 μm and a sheet diameter of 0.01-3.2 mm. The known production methods of glass flakes mainly include artificial blowing method, mechanical drawing method, mechanical blowing method, mechanical sheet throwing method, etc. The most commonly used production method is mechanical blowing method, which can produce glass flakes with good product quality and excellent performance. Generally speaking, the thinner the thickness of the glass flakes, for example, the glass flakes with a thickness of 2-10 μm, the better the product quality and the better the performance. In the present invention, the mesh number of the glass flakes used in the present invention is 10-400 mesh, more preferably 300-400 mesh.

[0075] When only silane coupling agent is used for surface treatment of glass flakes, it is easy for the anti-corrosion coating to absorb too much water during the construction process, and problems such as coating expansion, cracking, and peeling of the coating and the substrate material will occur in a short period of time. This phenomenon is more likely to occur especially for fine glass flakes with a mesh size in the range of 300-400. Although the addition of conventional epoxy diluents (such as 1,6-ethylene glycol diglycidyl ether) can alleviate the above phenomenon, the effect is still not good.

[0076] In the glass flake amorphous alloy composite anticorrosive composition of the present invention, the present invention performs surface modification treatment on the glass flakes via a mixed solution of a silane coupling agent and a diluent shown in formula (I). Compared with using only a silane coupling agent as a surface modifier, the diluent added in the present invention can reduce the viscosity of the anticorrosive coating, making the glass flakes more easily dispersed in the resin system, especially for the fine glass flakes with a mesh size in the range of 300-400 used in the present invention, the scheme of the present invention is used to form a low-viscosity anticorrosive coating, and it is not easy to cause the problem of large water absorption and high viscosity due to fineness, which is more conducive to construction. In particular, the double bond structure in the molecular structure of the cardanol diluent preferably used in the present invention can further improve the dilution efficiency.

[0077] Moreover, the active groups (such as hydroxyl, carboxyl, etc.) on the surface of the glass flakes with a lamellar structure form a coupling with the -O- in the molecular formula of the silane coupling agent and the diluent shown in formula (I), which not only greatly improves the compatibility of the glass flakes in the coating and increases the amount of glass flakes added, but also makes it easier for the glass flakes to be distributed in parallel in the anti-corrosion coating system, so that the glass flakes are more exposed in the anti-corrosion coating system, which can improve the reaction activity of the surface of the glass flakes, and is beneficial to improving the bonding force between the glass flakes and the matrix resin in the anti-corrosion coating, thereby improving the anti-corrosion and mechanical properties of the coating.

[0078] In addition, the silane coupling agent and diluent shown in formula (I) used in the present invention for forming the surface treatment of glass flakes preferably use a silane coupling agent having a terminal glycidyl ether oxyalkyl group shown in formula (II) and a terminal epoxy cycloalkyl alkyl chemical structure shown in formula (III), and a cardanol diluent preferably used. The terminal epoxy groups in their chemical structures have the property of reacting with the curing agent in the anti-corrosion coating resin system, thereby improving the cross-linking density of the anti-corrosion coating, thereby improving the mechanical properties, water resistance and corrosion resistance of the anti-corrosion coating. The benzene ring structure and double bond structure on the cardanol diluent preferably used in the present invention can further improve the salt spray resistance, impact resistance, acid and alkali resistance, etc. of the anti-corrosion coating.

[0079] In the glass flake amorphous alloy composite anti-corrosion composition of the present invention, a solvent may also be added to the mixed solution of the silane coupling agent and the diluent shown in formula (I). The optional solvent may be, for example, dibutyl ether, xylene, n-butanol or 4-methyl-2-pentanone. Other conventional solvents are also within the scope of protection of the present invention and are not limited here.

[0080] In the glass flake amorphous alloy composite anti-corrosion composition of the present invention, the glass flakes are surface treated by dipping or spraying a mixed solution containing a silane coupling agent shown in formula (I), a diluent and a solvent. From the perspective of surface treatment effect and treatment efficiency, dipping is preferably used, such as room temperature dipping. In order to further improve the surface treatment effect and treatment efficiency, the glass flakes can also be surface treated by dipping at a temperature of 40-80°C.

[0081] In the glass flake amorphous alloy composite anti-corrosion composition of the present invention, the mass ratio of glass flakes to the silane coupling agent and diluent represented by formula (I) is 1:(0.1-10):(0.1-10), preferably 1:(0.1-5):(0.1-5).

[0082] In the glass flake amorphous alloy composite anticorrosion composition of the present invention, the micron flaky amorphous alloy used in the present invention is an iron-based amorphous alloy Fe having a lamellar structure and a particle size of 10-50 μm (for example, 10-20 μm, 20-30 μm, 30-40 μm, 40-50 μm, etc., preferably 20-30 μm). α M β Alloy, wherein M is selected from at least one of the elements Cr, P, C, B, N, Co, Si, Cu, V, Al, Ti, Ta, Nb, Zr, Mo and Ni, α and β are atomic percentages, 55≤α≤80, 20≤β≤45, α+β=100.

[0083] Amorphous alloys are also called metallic glass (MG). Their internal atomic arrangement is chaotic and disordered, and their microstructure is characterized by long-range disorder and short-range order. They are formed when the liquid metal atoms in the molten state do not have time to rearrange themselves during the high-speed cooling process and retain the liquid state in the solid state. Traditional iron-based metal materials have crystal defects such as dislocations, grain boundaries or component segregation, which greatly shortens their service life in a corrosive environment. However, the homogeneous structure of amorphous alloys reduces the inducing zone of corrosion behavior, thereby improving corrosion resistance. At present, the main method to improve the corrosion resistance of amorphous alloys is to add corrosion-resistant elements with high chemical stability. Common elements are Cr, Ni, Nb, Si, P, etc.

[0084] There are two commonly used methods for preparing amorphous alloy powders: atomization and mechanical ball milling. The atomization method uses a fast-moving fluid (gas or liquid) to disperse the molten metal liquid into small droplets, and then quickly cools it to obtain amorphous powder. The amorphous powder prepared by this method has a smooth surface, uniform structure, good sphericity, and high particle dispersion, but the cost is relatively high. Compared with the non-equilibrium process of preparing amorphous alloys by rapid condensation, the mechanical ball milling process is a metastable equilibrium process. Common mechanical ball milling devices include planetary, stirring, and vibration types. High ball milling speed and continuous ball milling are more conducive to the preparation of amorphous alloys.

[0085] The method for preparing amorphous alloy powder by mechanical ball milling comprises the following steps: firstly, an amorphous alloy strip is prepared by single-roller rapid quenching strip spinning technology, and a completely molten alloy liquid is sprayed onto a high-speed rotating copper roller to form an amorphous alloy strip with a thickness of about 21-27 μm and a width of about 1-1.5 mm, and then the amorphous alloy strip is ball milled in a ball milling tank at a ball milling speed of, for example, 200 r / min, and a ball-to-material ratio of, for example, 20:1. During the mechanical ball milling process, the amorphous strip continuously collides with the grinding ball and the tank wall, and the external energy is continuously transmitted to the amorphous strip, so that the amorphous The energy accumulated inside the alloy continues to increase. When the atoms obtain enough energy, they will gradually and slowly move to the equilibrium position, resulting in structural relaxation, causing the free volume content of the amorphous to decrease, and the amorphous ribbon to become brittle and easier to break. The longer the ball milling time, the more energy is transmitted. At the same time, the temperature rise effect makes the amorphous ribbon crushing effect more obvious. The broken amorphous powder particles are irregular lamellar. The amorphous strips do not change their amorphous structural characteristics after ball milling, but are broken into micron-sized fine powder. The specific surface area of ​​the powder increases, and the number of "activated" planar sites in the particles increases.

[0086] According to the solution of the present invention, the present invention converts the micron-sized flaky amorphous alloy Fe α M βFor use in anti-corrosion coatings, M is preferably selected from one or more of the elements Cr, P, C, B, Si, Cu, Nb and Ni. The combination of these elements and Fe to form an amorphous alloy has been shown to have higher corrosion resistance. For example, Fe with a particle size of 20-30 μm used in the embodiment of the present invention 72 Cr8P5C5B 10 , Fe 72 Cr8P 10 C5B5、Fe 72 Cr8P5C 10 B5 or Fe 76 Si6B8P9Cu1.

[0087] According to the scheme of the present invention, in the glass flake amorphous alloy composite anti-corrosion composition of the present invention, the glass flakes and the micron-flaky amorphous alloy used are both flaky structures, and are applied to anti-corrosion coatings. The present invention uses a mixed solution of a surfactant and a diluent represented by formula (I) to perform surface treatment on the glass flakes, so that the glass flakes are easier to disperse and are more easily distributed in parallel in the anti-corrosion coating system. When combined with the micron-flaky amorphous alloy, they can be arranged layer by layer in the coating to form a maze-like structure, reduce the porosity of the coating, enhance the density of the coating, and hinder corrosion. The penetration of corrosive media can significantly improve the anti-penetration performance and corrosion life of the coating, and the glass flakes and micron-flaky amorphous alloys have high hardness, which can enhance the wear resistance of the coating. At the same time, the glass flakes show excellent tolerance in acid and alkali environments, which can enhance the acid and alkali resistance of the coating, and the micron-flaky amorphous alloy itself has high corrosion resistance. In the dynamic potential polarization curve, its corrosion potential and polarization potential are more positive, and it has a wider passivation range. Its corrosion products can overlap and be deposited between the pores of the coating for self-repair, further enhancing the salt spray resistance of the coating. Therefore, the composite anti-corrosion composition comprising glass flakes and micron-flaky amorphous alloys used in the present invention can synergistically enhance the salt spray resistance, acid and alkali resistance, wear resistance and other properties of the coating.

[0088] <Anti-corrosion coating>

[0089] The present invention further provides an anti-corrosion coating comprising the glass flake amorphous alloy composite anti-corrosion composition as described above.

[0090] The anticorrosive coating of the present invention may also include the following conventional components:

[0091] (1) Thermosetting resins: such as epoxy resins, phenolic resins, acrylic resins, polyurethane resins, silicone resins, etc., and their curing agents;

[0092] (2) Inorganic pigments, organic pigments, dispersants, defoaming agents, film-forming aids, surfactants, pH adjusters, thickeners, thixotropic agents, leveling agents, preservatives, etc.

[0093] The above-mentioned anti-corrosion coating of the present invention is coated on different substrates (such as steel substrates) and cured to form an anti-corrosion coating. Different resin systems and additive components are selected according to different anti-corrosion requirements.

[0094] In particular, in the present invention, the present invention particularly provides an epoxy anticorrosive coating, comprising component A and component B, wherein:

[0095] Component A includes the following raw materials in parts by weight:

[0096]

[0097] Component B includes the following raw materials in parts by weight:

[0098] 9-12 parts by weight of curing agent;

[0099] Adhesion promoter 1-2 parts by weight.

[0100] In the above-mentioned epoxy anti-corrosion coating of the present invention, the epoxy resin used in the present invention is a conventional epoxy resin that can be cured at room temperature, such as ether-type bisphenol-type epoxy resin, linear phenolic epoxy resin, aliphatic epoxy resin, aromatic epoxy resin, cyclic aliphatic epoxy resin, etc. The more commonly used are ether-type bisphenol-type epoxy resins, such as bisphenol A epoxy resin or bisphenol F epoxy resin, with an epoxy equivalent of 350-600g / eq.

[0101] In the above-mentioned epoxy anticorrosive coating of the present invention, the pigments and fillers used in the present invention can not only provide the required color and hiding power, but also improve the wear resistance of the anticorrosive coating, improve the fluidity of the anticorrosive coating, etc., including but not limited to: zinc phosphate, aluminum tripolyphosphate, titanium dioxide, zinc oxide, barium sulfate, talcum powder, etc. The additives used in the present invention have the functions of promoting the dispersion of pigments and fillers, adjusting the viscosity of the coating, promoting the parallel arrangement of glass flakes and amorphous alloys, and eliminating bubbles in the coating, including but not limited to dispersants, thickeners, defoamers or leveling agents, etc., and some well-known additive products can be used.

[0102] In the above-mentioned epoxy anticorrosive coating of the present invention, the curing agent used in the present invention is a common curing agent for epoxy resin, which can be cured at room temperature, including but not limited to phenolic amide curing agents, polyamide curing agents or phenolic amine curing agents, such as amine epoxy resin curing agents. According to the scheme of the present invention, when the epoxy resin of component A is mixed with the curing agent of component B, the active groups in the curing agent react with the epoxy groups in the epoxy resin to form new chemical bonds and produce a cross-linking reaction, thereby forming the matrix of the anticorrosive coating.

[0103] In the above-mentioned epoxy anticorrosive coating of the present invention, the adhesion promoter used in the present invention is used to improve the adhesion of the coating film on the surface of, for example, a steel substrate, and includes but is not limited to silane coupling agents, modified polyesters or acid copolymers.

[0104] The present invention further provides a method for preparing the epoxy anticorrosive coating as described above, comprising the following steps:

[0105] Step (1), mixing and dispersing glass flakes in a mixed solution of a diluent, a surfactant and a solvent, and standing or stirring the mixture at a speed of 400-800 rpm for 15-45 minutes to obtain a sol mixture of surface-modified glass flakes;

[0106] Step (2), mixing the dispersant, epoxy resin, pigment and filler with the sol mixture of glass flakes obtained in step (1), stirring at a speed of 1000-1500 rpm for 45-60 min, then adding micron-flaky amorphous alloy, thickener, leveling agent and defoaming agent at a speed of 800-1000 rpm, stirring for 10-20 min, and obtaining component A;

[0107] Step (3), mixing the adhesion promoter and the curing agent, stirring at a speed of 1000-1500 rpm for 5-10 minutes, to obtain component B;

[0108] Step (4), during construction, the component A obtained in step (2) and the component B obtained in step (3) are mixed, and stirred at a speed of 1000-1500 rpm for 5-10 minutes to obtain an anti-corrosion coating.

[0109] The above-mentioned epoxy anti-corrosion coating of the present invention is applied on different substrates (such as steel substrates) and cured to obtain an anti-corrosion coating. In some embodiments, the coating is performed by, for example, a sprayer, a roller, a brush, etc.

[0110] The glass flake amorphous alloy composite anti-corrosion composition and the anti-corrosion coating including the composition provided by the present invention have excellent comprehensive properties (including wear resistance, adhesion, salt spray resistance, impact resistance, acid and alkali resistance, etc.) prepared under the synergistic interaction of the surface-modified glass flakes and the micron-shaped flaky amorphous alloy. Compared with organic solvent epoxy zinc-rich anti-corrosion coatings, it has significant performance advantages, and the preparation process is simple, which is suitable for large-scale promotion and application.

[0111] The present invention is further described below in conjunction with the embodiments, the purpose of which is to better understand the content of the present invention and embody the essential characteristics of the present invention, so the examples given should not be regarded as limiting the scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention.

[0112] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0113] Embodiment 1:

[0114] In this example, a glass flake amorphous alloy composite anti-corrosion coating is prepared by the following scheme:

[0115] S1. Add 10 parts by weight of a diluent (chemical formula is as follows, viscosity is 30-115 mPa·s), 0.5 parts by weight of a surfactant (3-glycidyloxypropyltrimethoxysilane), and 6 parts by weight of glass flakes (300 mesh) to 15 parts by weight of a solvent (10 parts by weight of xylene, 3 parts by weight of n-butanol, and 2 parts by weight of 4-methyl-2-pentanone), and stir at 500 rpm for 30 min to obtain a surface-modified glass flake mixture;

[0116]

[0117] S2, 1 part by weight of dispersant (BYK-9076), 35 parts by weight of epoxy resin (Dow DER642U, epoxy equivalent of 500-560 g / eq), 20 parts by weight of pigments (5 parts by weight of zinc phosphate, 3 parts by weight of aluminum tripolyphosphate, 8 parts by weight of titanium dioxide, 4 parts by weight of barium sulfate) are added to the glass flake mixture obtained in step S1, and stirred at 1000 rpm for 60 min, and then 10 parts by weight of micron-shaped flaky amorphous alloy (Fe 2 O 2 ) is added at 1000 rpm. 72 Cr8P5C5B 10 , particle size 25 μm), 0.5 parts by weight of thickener (BYK-410), 1 part by weight of leveling agent (BYK-354), 1 part by weight of defoamer (BYK-1765), and stirred for 20 minutes to obtain component A;

[0118] S3, adding 1 part by weight of an adhesion promoter (a silicon-free acidic copolymer, Merck MOK-7614, Germany) to 10 parts by weight of a curing agent (Junjiang D650A), and stirring at 1000 rpm for 5 min to obtain component B;

[0119] S4. Mix the component A obtained in step S2 and the component B obtained in step S3, and stir them at a rotation speed of 1500 rpm for 5 minutes to obtain a glass flake amorphous alloy composite anti-corrosion coating.

[0120] Embodiment 2:

[0121] In this example, a glass flake amorphous alloy composite anti-corrosion coating is prepared by the following scheme:

[0122] S1. Add 5 parts by weight of a diluent (chemical formula is as follows, viscosity is 40-60 mPa·s), 1 part by weight of a surfactant (3-glycidyloxypropyltriethoxysilane), and 8 parts by weight of glass flakes (400 mesh) to 20 parts by weight of a solvent (10 parts by weight of dibutyl ester, 5 parts by weight of xylene, 3 parts by weight of n-butanol, and 2 parts by weight of 4-methyl-2-pentanone), and stir at 400 rpm for 45 min to obtain a surface-modified glass flake mixture;

[0123]

[0124] S2, 1 part by weight of dispersant (ECO-2900), 37 parts by weight of epoxy resin (Dow DER 6508, epoxy equivalent of 380-420 g / eq), 17 parts by weight of pigments and fillers (6 parts by weight of titanium dioxide, 3 parts by weight of zinc oxide, 5 parts by weight of barium sulfate, 3 parts by weight of talc) are added to the glass flake mixture obtained in step S1, and stirred at 1500 rpm for 45 min, and then 9 parts by weight of micron-shaped flaky amorphous alloy (Fe 2 O 2 ) is added at 800 rpm. 72 Cr8P 10 C5B5, particle size 30 μm), 0.5 parts by weight of thickener (Hemmings THIXATROL PLUS), 0.5 parts by weight of leveling agent (Huitu HT-403), 1 part by weight of defoamer (Hemmings Defom 2700), and stirred for 10 minutes to obtain component A;

[0125] S3, adding 1.5 parts by weight of an adhesion promoter (modified polyester, Evonik Addbond LP 1611) to 11 parts by weight of a curing agent (Evonik Ancamide 2050), and stirring at a rotation speed of 1500 rpm for 10 min to obtain component B;

[0126] S4. Mix the component A obtained in step S2 and the component B obtained in step S3, and stir them at a rotation speed of 1000 rpm for 10 minutes to obtain a glass flake amorphous alloy composite anti-corrosion coating.

[0127] Embodiment 3:

[0128] In this example, a glass flake amorphous alloy composite anti-corrosion coating is prepared by the following scheme:

[0129] S1. Add 12 parts by weight of a diluent (chemical formula is as follows, viscosity is 2000 mPa·s), 0.5 parts by weight of a surfactant (3-glycidyloxypropylmethyldimethoxysilane), and 5 parts by weight of glass flakes (325 mesh) to 13 parts by weight of a solvent (10 parts by weight of xylene, 2 parts by weight of n-butanol, and 1 part by weight of 4-methyl-2-pentanone), and stir at 800 rpm for 15 min to obtain a surface-modified glass flake mixture;

[0130]

[0131] S2, 1 part by weight of dispersant (BASF Efka PX 4703), 32 parts by weight of epoxy resin (Baling Petrochemical CYD-011, 454-555 g / eq), 22 parts by weight of pigments and fillers (4 parts by weight of zinc phosphate, 4 parts by weight of aluminum tripolyphosphate, 6 parts by weight of titanium dioxide, 6 parts by weight of barium sulfate, 2 parts by weight of talc) are added to the glass flake mixture obtained in step S1, and stirred at 1200 rpm for 50 min, and then 12 parts by weight of micron-shaped flaky amorphous alloy (Fe 2O 4 ) is added at 800 rpm. 72 Cr8P 10 C5B5, particle size 20 μm), 0.5 parts by weight of a thickener (XUHUAC AKN-7010), 1 part by weight of a leveling agent (Dow Corning DC-29), and 1 part by weight of a defoaming agent (BYK-A530), and stirred for 15 minutes to obtain component A;

[0132] S3, adding 2 parts by weight of adhesion promoter (modified polyester, Evonik AddBond LTW-B) to 9 parts by weight of curing agent (Cardolite LITE 3060), stirring at 1200 rpm for 8 min to obtain component B;

[0133] S4. Mix the component A obtained in step S2 and the component B obtained in step S3, and stir at a rotation speed of 1000 rpm for 9 minutes to obtain a glass flake amorphous alloy composite anti-corrosion coating.

[0134] Embodiment 4:

[0135] In this example, a glass flake amorphous alloy composite anti-corrosion coating is prepared by the following scheme:

[0136] S1. Add 8 parts by weight of a diluent (chemical formula is as follows, 40-70 mPa·s), 1 part by weight of a surfactant (3-glycidyloxypropylmethyldiethoxysilane), and 7 parts by weight of glass flakes (400 mesh) to 18 parts by weight of a solvent (15 parts by weight of dibutyl ester, 3 parts by weight of xylene), and stir at 600 rpm for 40 min to obtain a surface-modified glass flake mixture;

[0137]

[0138] S2, 0.5 parts by weight of dispersant (BYK-9076), 40 parts by weight of epoxy resin (Dow DER671, 475-550 g / eq), 16 parts by weight of pigments (6 parts by weight of zinc phosphate, 6 parts by weight of titanium dioxide, 4 parts by weight of talc) were added to the glass flake mixture obtained in step S1, stirred at 1300 rpm for 45 min, and then 8 parts by weight of micron-shaped flaky amorphous alloy (Fe 2 O 2 ) was added at 900 rpm. 76 Si6B8P9Cu1, particle size 30μm), 0.2 parts by weight of thickener (Fenghong BP-183B), 0.5 parts by weight of leveling agent (Yihua 3033A), 0.8 parts by weight of defoamer (TEGO Airex900), stirred for 13 minutes to obtain component A;

[0139] S3, adding 1 part by weight of adhesion promoter (3-aminopropyltrimethoxysilane, ADAMA KH540) to 12 parts by weight of curing agent (Cardolite NX-2003D), stirring at 1300 rpm for 7 min to obtain component B;

[0140] S4. Mix the component A obtained in step S2 and the component B obtained in step S3, and stir them at a rotation speed of 1200 rpm for 6 minutes to obtain a glass flake amorphous alloy composite anti-corrosion coating.

[0141] Embodiment 5:

[0142] In this example, a glass flake amorphous alloy composite anti-corrosion coating is prepared by the following scheme:

[0143] S1. Add 9 parts by weight of a diluent (chemical formula is as follows, viscosity is 40-70 mPa·s), 1 part by weight of a surfactant (2-(3,4-epoxycyclohexyl)ethyltriethoxysilane), and 5 parts by weight of glass flakes (325 mesh) to 17 parts by weight of a solvent (10 parts by weight of dibutyl ester, 7 parts by weight of 4-methyl-2-pentanone), and stir at 700 rpm for 25 min to obtain a surface-modified glass flake mixture;

[0144]

[0145] S2, 1 part by weight of dispersant (BYK-9076), 36 parts by weight of epoxy resin (Nan Ya NPES-901, 450-500 g / eq), 19 parts by weight of pigments (5 parts by weight of aluminum tripolyphosphate, 7 parts by weight of titanium dioxide, 7 parts by weight of barium sulfate) are added to the glass flake mixture obtained in step S1, stirred at 1400 rpm for 48 min, and then 9 parts by weight of micron-shaped flaky amorphous alloy (Fe 2 O 2 ) is added at 950 rpm. 72 Cr8P5C 10 B5, particle size 25 μm), 1 part by weight of thickener (Joshida Chemical J0602), 1 part by weight of leveling agent (BYK Chemical BYK-333), 1 part by weight of defoamer (Merck MOK-6621), stirred for 14 minutes to obtain component A;

[0146] S3, adding 1.5 parts by weight of an adhesion promoter (aminopropyl triethoxysilane, Dow Corning OFS-6011) to 10 parts by weight of a curing agent (Junjiang D8115A), and stirring at a speed of 1400 rpm for 6 min to obtain component B;

[0147] S4. Mix the component A obtained in step S2 and the component B obtained in step S3, and stir them at a rotation speed of 1300 rpm for 7 minutes to obtain a glass flake amorphous alloy composite anti-corrosion coating.

[0148] Comparative Example 1:

[0149] Based on Example 1, no micron-flaky amorphous alloy is added.

[0150] Comparative Example 2:

[0151] Based on Example 1, step S1 is omitted, and the surface-modified glass flake mixture is not added in step S2.

[0152] Comparative Example 3:

[0153] In this example, the epoxy zinc-rich anticorrosive coating is prepared by the following scheme:

[0154] S1. Add 22 parts by mass of epoxy resin (Dow DER 642U, 500-560 g / eq), 61 parts by mass of zinc powder (Daxiao Chemical, 800 mesh), 1 part by mass of thickener (BYK-410), 1 part by mass of leveling agent (BYK-354), and 1 part by mass of defoamer (BYK-1765) to 15 parts by mass of solvent (13 parts by mass of xylene and 2 parts by mass of n-butanol), and stir at a speed of 1000 rpm for 60 min to obtain component A;

[0155] S2, adding 1 part by mass of adhesion promoter (silicon-free acidic copolymer, Merck MOK-7614, Germany) to 5 parts by mass of curing agent (Junjiang D650A), stirring at 1000 rpm for 5 min to obtain component B;

[0156] S3. Mix the component A obtained in step S1 and the component B obtained in step S2, and stir at a rotation speed of 1500 rpm for 5 minutes to obtain an epoxy zinc-rich coating.

[0157] The anti-corrosion coatings prepared in Examples 1-5 and Comparative Examples 1-3 were used to prepare test samples according to the standard "GB / T 9271-2008 Standard Test Plates for Paints and Varnishes", and the adhesion, wear resistance, impact resistance, salt spray resistance, acid resistance and alkali resistance were tested accordingly. Among them, the adhesion test is based on "GB / T 5210-2006 Paint and varnish pull-off adhesion test"; the wear resistance test is based on "GB / T 1768-2006 Paint and varnish wear resistance determination rotating rubber grinding wheel method" using 1000g / 1000r, grinding wheel model CS-17; the impact resistance test is based on "GB / T 1732-2020 Paint film impact resistance determination method", the weight of the hammer is 1000g; the salt spray resistance test is based on "GB / T 1771-2007 Paint and varnish resistance to neutral salt spray performance determination"; the acid and alkali resistance tests are based on "GB / T 9274-1988 Paint and varnish resistance to liquid media test", using 5% sulfuric acid solution and 5% sodium hydroxide solution respectively. The test results are shown in Table 1.

[0158] Table 1

[0159]

[0160]

[0161] As can be seen from Table 1, from the comparison of the glass flake amorphous alloy composite anticorrosion coating of Examples 1-5 and the anticorrosion coating without micron-flaky amorphous alloy in Comparative Example 1 and the anticorrosion coating without glass flake in Comparative Example 2, it can be seen that there is a synergistic interaction between the glass flakes and the micron-flaky amorphous alloy in the glass flake amorphous alloy composite anticorrosion coating, and the two have a synergistic promotion effect on the comprehensive properties of the enhanced coating (such as adhesion, wear resistance, impact resistance, salt spray resistance, acid resistance, alkali resistance, etc.). Compared with the traditional organic solvent epoxy zinc-rich anticorrosion coating of Comparative Example 3, the glass flake amorphous alloy composite anticorrosion coating of Examples 1-5 of the present invention has significant performance advantages. Compared with the conventional active diluent used in Example 4, the wear resistance and salt spray resistance of the glass flake amorphous alloy composite anticorrosion coating using the cardanol active diluent in Example 5 are better than those in Example 4.

[0162] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A glass flake amorphous alloy composite anticorrosion composition, characterized in that: The invention comprises a micron-shaped amorphous alloy and glass flakes surface-modified by a mixed solution of a surfactant and a diluent as shown in formula (I): In the formula, R1, R2, and R3 are each independently selected from an alkyl group or an alkoxy group, wherein the alkyl group in the alkyl group or the alkoxy group is selected from a C1-C8 alkyl group, preferably a C1-C4 alkyl group, more preferably a methyl group, an ethyl group, a methoxy group, or an ethoxy group, wherein R1, R2, and R3 are the same or different, and at least one of R1, R2, and R3 is an alkoxy group; R4 is selected from a substituted or unsubstituted C1-C 12 The alkyl group is an alkyl group, an aralkyl group or a cycloalkyl group, preferably a C1-C8 alkyl group, an aralkyl group or a cycloalkyl group.

2. The glass flake amorphous alloy composite anticorrosive composition according to claim 1, characterized in that: R4 is selected from the group consisting of a terminal glycidyl ether oxyalkyl group represented by formula (II) and a terminal epoxy cycloalkyl alkyl group represented by formula (III): In formula (II), R5 is a C1-C8 alkyl group; In formula (III), R6 is a C1-C8 cycloalkyl group.

3. The glass flake amorphous alloy composite anticorrosive composition according to claim 1 or 2, characterized in that: The surfactant is a silane coupling agent, selected from at least one of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; the diluent is selected from at least one of an active diluent and an inactive diluent, the active diluent is preferably a glycidyl ether diluent, more preferably a cardanol glycidyl ether diluent, the inactive diluent is preferably selected from at least one of cardanol and ethylene glycol monocardanol ether; preferably, the viscosity of the diluent is 5-2000 mPa·s (25°C).

4. The glass flake amorphous alloy composite anticorrosive composition according to claim 3, characterized in that: The mixed solution also includes a solvent. Preferably, the solvent is selected from at least one of dibutyl ether, xylene, n-butanol and 4-methyl-2-pentanone.

5. The glass flake amorphous alloy composite anticorrosive composition according to claim 4, characterized in that: The glass flakes are surface treated with the mixed solution by dipping or spraying, preferably by dipping, and more preferably by dipping at room temperature.

6. The glass flake amorphous alloy composite anticorrosive composition according to claim 1, characterized in that: The micron-sized flaky amorphous alloy is Fe having a lamellar structure. α M β Alloy, wherein M is selected from at least one of the elements Cr, P, C, B, N, Co, Si, Cu, V, Al, Ti, Ta, Nb, Zr, Mo and Ni, preferably, M is selected from at least one of the elements Cr, P, C, B, Si, Cu, Nb and Ni, α and β are atomic percentages, 55≤α≤80, 20≤β≤45, α+β=100; preferably, the particle size of the micron-shaped flaky amorphous alloy is 10-50μm, preferably 20-30μm.

7. An anticorrosive coating, characterized in that: It comprises the glass flake amorphous alloy composite anti-corrosion composition as described in any one of claims 1 to 6.

8. The anticorrosive coating according to claim 7, characterized in that: The anticorrosive coating comprises component A and component B, wherein: Component A includes the following raw materials in parts by weight: Component B includes the following raw materials in parts by weight: 9-12 parts by weight of curing agent; Adhesion promoter 1-2 parts by weight.

9. The anticorrosive coating according to claim 8, characterized in that: The epoxy resin is selected from at least one of bisphenol A epoxy resin and bisphenol F epoxy resin, and the epoxy equivalent is 350-600g / eq; the pigment and filler are selected from at least one of zinc phosphate, aluminum tripolyphosphate, titanium dioxide, zinc oxide, barium sulfate and talcum powder; the auxiliary agent is selected from at least one of a dispersant, a thickener, a defoamer and a leveling agent; the curing agent is selected from at least one of a phenolic amide curing agent, a polyamide curing agent and a phenolic amine curing agent; the adhesion promoter is selected from at least one of a silane coupling agent, a modified polyester and an acid copolymer.

10. A method for preparing an anticorrosive coating according to any one of claims 7 to 9, characterized in that: The steps include: Step (1), mixing and dispersing glass flakes in a mixed solution of a diluent, a surfactant and a solvent, and standing or stirring the mixture at a speed of 400-800 rpm for 15-45 minutes to obtain a sol mixture of surface-modified glass flakes; Step (2), mixing the dispersant, epoxy resin, pigment and filler with the sol mixture of glass flakes obtained in step (1), stirring at a speed of 1000-1500 rpm for 45-60 min, then adding micron-flaky amorphous alloy, thickener, leveling agent and defoaming agent at a speed of 800-1000 rpm, stirring for 10-20 min, and obtaining component A; Step (3), mixing the adhesion promoter and the curing agent, stirring at a speed of 1000-1500 rpm for 5-10 minutes, to obtain component B; Step (4), during construction, the component A obtained in step (2) and the component B obtained in step (3) are mixed, and stirred at a speed of 1000-1500 rpm for 5-10 minutes to obtain an anti-corrosion coating.

Citation Information

Patent Citations

  • Anticorrosion coating used for renovating steel structure bridge

    CN108102513A

  • Heavy anti-corrosion coating and application thereof

    CN111253832A

  • Low-density anticorrosive paint and preparation method thereof

    CN116396669A

  • Solvent-free graphene amorphous composite anticorrosive paint and preparation method thereof

    CN118620476A